Risk Factors of Cognitive Decline in Older Caregivers With HIV: An Emerging Hypothesis. (14th November 2022) - Vance, David E.; Lee, Yookyong; Batey, D. Scott; Puga, Frank; Clay, Olivio J.; Byun, Jun Y.; Long, Alexis R.; Rafford, Meghan; Xiao, Chunhong; Fazeli, Pariya L.
Abstract: People with HIV (PWH) are living longer and healthier lives; thanks to combination antiretroviral therapy. As many PWH age, they find themselves providing care to family members and friends, just as their counterparts without HIV. The literature indicates that becoming a caregiver creates conditions that compromise one's cognitive function. Additionally, nearly 45% of all PWH experience HIV-associated neurocognitive disorder and are already vulnerable to cognitive impairment due to HIV, aging, and accompanying health conditions, and lifestyle factors. Given what is known, we assert that caregivers with HIV, especially as they age, are at additional risk for developing cognitive impairments. The purpose of this commentary was to briefly examine the juxtaposition between cognitive vulnerability of caregiving and the cognitive vulnerability of aging with HIV. Potential factors contributing to impaired cognition include stress, lack of social support, stigma, lifestyle, and comorbidities. Implications for clinical practice and research are provided.